Patterns of medication use by chronic and episodic headache sufferers in the general population: Results from the frequent headache epidemiology study - Scher, AI; Lipton, RB; Stewart, WF; Bigal, M (Cephalalgia, 2010)
Though symptomatic medication overuse is believed to play a role in progression from episodic headaches (EH) to chronic daily headaches (CDH), population-based data on this topic are limited. Our objective was to describe patterns of medication use among CDH and EH sufferers in a general population sample. We compared medications used to treat headache in CDH cases and EH controls identified from a large population-based computer-assisted telephone interview survey. CDH began within 5 years of the computer-assisted telephone interview. Questions on medication use focused on treatment prior to the onset of CDH for cases and on an equivalent period in the past for controls. We asked about the likelihood of treating, time waiting to treat, number of different medications used, first, second and third most frequently used headache pain medication, and total treatment days. Questions were also asked about the use of medication for non-headache pain. Current treatment patterns and past treatment patterns were assessed. Likelihood of use of specific medications was compared between CDH cases and EH controls after adjusting for age, sex, primary headache type and number of medications taken to treat pain. Our sample consists of 206 CDH cases and 507 EH controls. CDH subjects were more likely than EH controls to use over-the-counter/caffeine combination products, triptans, opioid compounds and ‘other’ prescription pain medications. Use of aspirin was protective. After adjustment, aspirin and ibuprofen were (negatively) associated with CDH [OR = 0.5 (0.3–0.9), OR = 0.7 (0.5–1.0)] and opioids remained positively associated with CDH [OR = 2.3 (1.3–3.9)]. For past use, CDH was positively associated with over-the-counter/caffeine combination products and opioid compounds and was negatively associated with use of aspirin. Only ibuprofen remained (negatively) associated with CDH after adjustment [OR = 0.6 (0.4–0.9)]. After adjusting for demographic factors, primary headache type and number of medications taken, CDH sufferers are more likely to use opioid-combination analgesics, and less likely to use aspirin or ibuprofen, than EH sufferers.